EVALUASI EKONOMI LAHAN PERTANIAN: PENDEKATAN NILAI MANFAAT MULTIFUNGSI LAHAN SAWAH DAN LAHAN KERING - . Irawan; Sanim B; Siregar H; Kurnia U (Jurnal Ilmu Pertanian Indonesia, 2006)
Agricultural lands not only produce food and fibre, but also generate social and economic services such as job opportunities, rural culture preservation, and food security, as well as environmental services such as flood mitigation, erosion and sedimentation preventions, water resource conservation, and biodervesity. The services are called multifunctionality. The out put of multifunctionality is public goods since the beneficiaries are not only farmers but also the publi at large. The value of environmental services produced by farmers, in general, is not accoundted in the current market mechanism, and in most casses is ignored in the policy making. This condition leas to lack of attractiveness of farming, which subsequently leads to conversion of agricultural lands. This paper presents research results on economic valuation on the multifunctionality of agricultural lands, particulary paddy fields and upland farming in Citarik Sub Watershed, Bandung District, West Java. The reulsts showed that using replacement cost method (RCM) the economic value (EV) of paddy fields and uplands were Rp. 55.4 million and Rp. 9.9 million/ha/year. Repectively. The EV of paddy fields consisted of environmental services (71.4%) and marketable products (18.6%). It means that farmers had provied free of charge environmental services to the society. The community’s knowledge on multifunctionality of agriculture based on interview ws still low. Around 66% of respondents recognized only one to two agricultural multifunctionality aspects.